EFFECT OF RECOVERY SUPPLEMENTARY FOOD PROGRAM ON NUTRITIONAL STATUS OF STUNTING TODDLERS AT CIMAHI CITY HEALTH CENTER APRIL-JULY 2021 - Elly Noer Rochman; Iis Inayati Rakhmat; Jihan Amalia; Maghvira Fazria Prilyadi (Fakultas Kedokteran Gigi Unjani, 2022)
The Provision of Supplementary Food Recovery or Pemberian Makanan Tambahan (PMT) recovery is one of the government programs in dealing with stunting cases in toddlers. This study was conducted to analyze changes in the nutritional status of children under five with BMI/U index before and after being given PMT-Recovery in the working area of ​ Cimahi City Health Center. This was an analytic observational study with a cross-sectional research design. The location of the research is in the working area of ​ Cimahi City Health Center. The research was conducted in October-December 2021 or two months after the PMT Recovery program was implemented. In this study, the population used was children under five years old in the working area of ​ Cimahi City Health Center who received PMT Recovery. The sample in this study was 33 children aged 6-59 months from the entire population who met the research inclusion criteria. Simple random sampling was used in this research. The nutritional status of children under five was checked using the anthropometric method of BB and TB, then BMI was calculated and then plotted using the WHO BMI/U index chart. The research targets were undernourished toddlers aged 6-59 months with a z-score of more than -2SD and malnourished toddlers aged 6-59 months who were given additional food. Statistical tests were performed using paired t-test with a significance level of <0.05. After three months of being given PMT Recovery, there was a decrease in the percentage of children under five with underweight nutritional status from 42.4% to 39.4%. There is a significant difference in the nutritional status of children under five based on BMI/U before and after PMT Recovery (p=0.05). There are differences in the nutritional status of children under five with BMI/U index before and after PMT-Recovery. DOI : 10.54052/jhds.v2n1.p53-62